40 years within two epochs of two millennia - Kordium, V.A. (Вiopolymers and Cell, 2013)
The article-generalization deals with the main directions being developed in the Department of Cell Regulatory Mechanisms during past 40 years from the moment of the Institute of Molecular Biology and Genetics of Academy of Sciences of Ukraine organization up to our days. The main steps of space and molecular biology in the USSR and future development of biology in Ukraine are presented in this review.